The differences between horizontal and vertical direction during a single-leg rebound jump: obtained using three-dimensional motion analysis - Kariyama, Y.; Zushi, K. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to clarify the differences between single-leg rebound jump for horizontal direction (HSJ) and vertical direction (VSJ) in terms of three-dimensional joint kinetics for the take-off leg focused on frontal plane movement. Eleven male track and field athletes were performed the HSJ and VSJ. Kinematics and kinetics data were recorded using Vicon T20 system (250 Hz) and force platforms (1000 Hz). In HSJ, as compared to VSJ, the joint kinetics characteristics are as follows: 1) the hip abduction torque and torque power around the adduction-abduction axis are larger; and 2) the trunk lateral flexion torque and torque power around the adduction-abduction axis are larger. Therefore, the hip adduction-abduction and trunk lateral flexion-extension movement plays an important role in a single-leg jump. Additionally, this is pronounced in HSJ as compared to VSJ.